Monitoring the Achievement of Environmental Sanitation Indicators at Pulau Kijang Health Center, Indragiri Hilir Regency - Zaman, Kamali; Winda, Septiani (Journal of Community Services and Engagement: Voice of Community (VOC), 2025)
Environmental sanitation is critical for public health as it affects the spread of diseases such as diarrhea, dengue, and respiratory infections. Poor sanitation arises from issues like inadequate access to clean water, insufficient waste disposal systems, and low public awareness. In Indragiri Hilir Regency, despite health programs, issues such as unsafe drinking water, inadequate latrines, and challenges in implementing Community-Based Total Sanitation (STBM) persist. This highlights problems in program execution, including limited resources and community involvement. The community service project was conducted in partnership with Pulau Kijang Health Center. It involved field data collection, interviews, and document review to assess sanitation progress. The monitoring focused on key indicators such as access to safe drinking water, healthy latrines, and waste management. The project concluded with training health staff and local cadres on sanitation evaluation based on data analysis. Initial assessments revealed that previous monitoring efforts were ineffective due to outdated data and a lack of integration. The approach included training for health workers and local cadres on community-based sanitation monitoring, developing a simple digital data recording system, and conducting public education campaigns. The introduction of the digital system improved data organization, and public education campaigns increased community involvement in reporting sanitation issues. Public participation rose significantly, leading to more accurate sanitation data and better monitoring techniques. The program successfully addressed issues such as outdated data and limited human resources through a comprehensive approach. The introduction of digital data systems and community education improved the quality and accessibility of sanitation data. This led to greater community participation and enhanced the capacity of health personnel. The project demonstrates the value of a collaborative, data-driven approach for sustainable improvements in public health and sanitation.